Photocatalytic oxidation of organic dyes and pollutants in wastewater using different modified titanium dioxides: A comparative review - Zangeneh, H. (Korean Society of Industrial Engineering Chemistry, 2015)
This article compares the effectiveness of pure and modified TiO2 for photocatalytic degradation of different organic matters and clarifies the advantages of the modified TiO2 with photoactivity under visible light. Photocatalytic degradation technique with titanium dioxide is generally applied for treating wastewater containing refractory organic contaminants with the purpose of reuse due to its ability to achieve complete mineralization of the compounds under mild conditions such as ambient temperature and pressure. Performance of different types of photocatalytic reactors, effects of important parameters on the reactors performance, effect of various methods used to enhance the photocatalytic activity of TiO2 including doping, sensitization of TiO2 and surface modification are discussed in details. So far, a few review papers have been published and extensive information have been reported on the structure and electronic properties of TiO2, difference between TiO2 with other common semiconductors used for photocatalytic applications, various methods used to enhance the photocatalytic characteristics of TiO2 including dye sensitization, doping, coupling, the effects of various operating parameters on the photocatalytic degradation of phenols and dyes and types of reactors, comparison between effective modes of TiO2 application as immobilized on surface or as suspension, and photocatalytic hybrid membrane system are presented. However, in the published review papers, performance of the different modified photocatalysts is rarely compared quantitatively. Therefore, in order to provide an inclusive and effective comparison among the studies, specific removal rate (SRR) (mgcompoundremoved/gcat.h) was calculated as a response. Â© 2014 The Korean Society of Industrial and Engineering Chemistry.